Aplicação de modelos cinéticos no processo de biossorção de zinco - Aguiar, Ana Beatriz Soares (2021)
The accumulation of zinc as well as several other metals in the environment is harmful to nature and human health. The zinc present in high concentrations in the human organism may be responsible for changes in the functioning of organs and systems. Among the main anthropogenic sources of this metal are agricultural and industrial activities. The adsorption using biological materials as adsorbents (biosorption) has shown satisfactory results for metal removal. Thus, kinetic modeling is essential to direct biosorption studies, since the equation and interpretation of results help in determining the rate of solute removal, in estimating the adsorption mechanism and in the design of reactors and systems of wastewater treatment. Different kinetic models of adsorption are described in the literature, among them, pseudo first order model, pseudo second order model, Weber and Morris model and Elovich model, which were used in this project. The work methodology was divided into two phases. The first was based on an experimental study of a zinc biosorption system evaluating the performance of an anaerobic biomass in its granular and powder form and subsequently the application of the kinetic study under the system. The second phase consisted of the application of kinetic modeling in other zinc biosorption systems by surveying studies published in the literature. Thus, it was possible to evaluate different zinc biosorption systems, through the application of different kinetic models, as well as the determination of kinetic parameters and the identification of the kinetic model that best represented the experimental data. Evaluating the parameters and the linear regression coefficient (R²), the kinetic data were better described by the pseudo second order model, where the biosorption system is based on chemical reactions and the limiting step of the process is due to chemical sorption.